Postoperative recurrence of plunging ranula: A case report and literature review - ZHANG Xin; DI Ruiling; LI Cong; WANG Ning; LI Xiangchun; LU Tongtong (Kouqiang hemian waike zazhi)
Plunging ranulas are relatively rare cystic mass in the neck, which are mucous extravasation or retention pseudocysts from the sublingual gland, without the epithelial linings. They plunge inferiorly into the neck by extending beyond the free edge of the mylohyoid muscles or through the dehiscences of the muscles. We report a case of plunging ranula treated in our hospital, with recurrence seven months after the intraoral sublingual gland excision. The literatures associated with pathogenesis, clinical presentation, differential diagnosis, surgical approach and recurrent causes are reviewed.